Hipótese da fragilidade financeira de Hyman Minsky: um estudo aplicado ao setor público subnacional - Caríssimo, Cláudio Roberto (2021)
When State management is carried out in an efficient and sensitive manner, it can be considered a public good. To achieve this desired efficiency, control and measurement are required. The Hypothesis of Financial Fragility Applied to the Public Sector (HFFSP), through the analysis of budget accounts, measures, presents and serves as an instrument for evidencing and even preventing fiscal crises. Its informational capacity is formed due to the possibility of evidencing situations of financial fragility, analyze causes of this fragility and assist in the estimation of fiscal risks in the process of budget planning. The general objective of this work is to present ways of using the HFFSP, which are able to assist the Brazilian states and municipalities in fiscal management. For this undertaking it was performed: an Integrative Literature Review on the Hypothesis of Financial Fragility and its application in the public sector; empirical analysis of the impacts of interest and amortization, as well as the other variables that make up the determination of the Public Sector Financial Position, through Structural Equation Modeling; verification of the causal relationships between the financial positions of the Brazilian states and the interest, amortization and current expenses and finally, suggestion of a model of application of the analysis of the financial positions arising from the HFFSP as a complement to the preparation of the Fiscal Risks Annex when preparing the LDO. The Integrative Literature Review enabled the composition of an integrated reasoning structure, assimilating the considerations of the various authors and reinforcing the propositions of Minsky's theory. It explained forms of its application and inference as to the most applied aspects. The studies on financial fragility addressed gaps in Keynesian theory related to the process of realization of firms' cash flow expectations, its relationship with financial crises and evidencing financial positions. The Structural Equation Modeling procedure, when analyzing the Brazilian states, evidenced that financial fragility is formed not only as a function of excessive current expenditures, but also due to interest and amortization expenditures that exceed the balance determined by comparing Current Revenues and Current Expenses. The analysis of the causal relations between the financial positions of the Brazilian states confirmed the causal influence of both Interest and Amortization, as well as Current Expenses on financial fragility. This study expands the discussions regarding financial fragility in the public sector, in light of Minsky, taking into account the specificities of the Brazilian reality as to fiscal lack of control and mistrusts as to the sustainability of the public debt. The HFFSP application model as a complement for the elaboration of the Fiscal Risks Annex supported by the Portfolio Theory framework proved to be pertinent. The results demonstrated that it can be a new option for measuring and estimating fiscal risk, as advocated in this paper. Thus, it was corroborated the thesis of this study regarding the applicability of HFFSP in assisting the Brazilian states and municipalities in fiscal management, through the indices and positions of financial fragility applied to the public sector.